1998
DOI: 10.1002/(sici)1098-2752(1998)18:2<137::aid-micr13>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber diameter and muscle type distribution following free microvascular muscle transfers: A prospective study

Abstract: The histology of free microvascular muscle flaps in 19 patients was studied prospectively. Biopsies were taken during operation, and after 2 and 6 weeks, as well as 3, 6, and 9 months, postoperatively, fixed and stained using the van Gieson method. Fiber diameters were analyzed morphometrically and fiber types defined immunohistochemically using myosin fast antibody. During the nine-month follow-up period, mean muscle fiber diameter decreased significantly (P < 0.01), type-1 fibers atrophied significantly (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
(45 reference statements)
3
22
0
2
Order By: Relevance
“…Denervation atrophy is reported in both the human and veterinary literature after free muscle transfer 16,21,35,56,57 . Atrophy following free tissue transfer is reported to be fiber type specific with preferential atrophy of type-1 muscle fibers 56 .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Denervation atrophy is reported in both the human and veterinary literature after free muscle transfer 16,21,35,56,57 . Atrophy following free tissue transfer is reported to be fiber type specific with preferential atrophy of type-1 muscle fibers 56 .…”
supporting
confidence: 88%
“…Atrophy following free tissue transfer is reported to be fiber type specific with preferential atrophy of type-1 muscle fibers 56 . Increased muscle atrophy is associated with prolonged immobilization and post-operative infection.…”
mentioning
confidence: 99%
“…In contrast with the well known rodent model (see above), one-year after spinal cord injury the LMN denervated human muscles still present simple atrophy. As was described in the rabbit model (see above), in a 60-case series of human vastus lateralis muscle biopsies from subjects suffering traumatic SCI, we observed that human muscle fibers undergo atrophy, not degeneration oneyear after LMN denervation [55,57], confirming and extending preliminary results of prospective bioptic studies of human free flap muscle transfers, which showed that at nine-month after surgery the denervated muscle fibers only decreased in size [53]. On the other hand, characteristic denervation-induced muscle fiber disorganization is documented by electron microscopy, much earlier than severe atrophy in both animal models [9,10], and humans [18,55,57], thus, explaining the early functional impairments of the LMN denervated muscle.…”
mentioning
confidence: 79%
“…Strong corroborating evidence was collected analyzing expression of myogenesis-related genes in denervated rat muscles [4,70,98]. Beside in LMN denervation due to SCI, regeneration of muscle fibers in human LMN denervated muscle had been reported in cases of free microvascular muscle transfers up to 4 years after surgery, when activation of satellite cells was evident [52,53]. In muscle biopsies harvested from three and more years after surgical transplant of free muscle flaps, among small muscle fibers, MHCemb-positive myofibers were demonstrated by the specific monoclonal antibody [97].…”
Section: Satellite Cell Activation Replication and Fusion Produce Rementioning
confidence: 99%
“…Only few papers have described LDM fiber type distribution using histochemical or immunohistochemical methods [13, 14, 16, 17, 19, 27, 28] and only one study has also considered the mechanical characteristics [13], although this aspect was not analysed extensively as the main focus was on the regeneration and reinnervation processes.…”
Section: Discussionmentioning
confidence: 99%